Ethnomedicinal plants used for the treatment of dermatological affections on the Purépecha Plateau, Michoacán, Mexico - Esquivel-García, Roberto; Pérez-Calix, Emmanuel; Ochoa-Zarzosa, Alejandra; García-Pérez, Martha Estrella (Instituto de Ecología, A.C., 2018)
Background and Aims: Inhabitants of the Purépecha Plateau preserve an excellent ancestral knowledge on medicinal plants used for dermatological affections, which has not been documented. An ethnopharmacological survey was carried out in this region to gather information on the use of medicinal plants and herbal preparations for treating dermatological affections, to disseminate the Purépecha indigenous knowledge and identifying promising plants for developing new formulations for cutaneous conditions.Methods: The study was conducted in the 21 municipalities that compose the Purépecha Plateau. A total of 86 local inhabitants (62 women and 24 men) were interviewed. The data were quantitatively analyzed through the determination of the use value, fidelity level and informant consensus factor.Key results: A total of 97 plant species belonging to 47 families were documented for treating 19 dermatological conditions on the Purépecha Plateau. Asteraceae was the leading family among the collected medicinal plants (20.61%), followed by Lamiaceae (13.40%) and Solanaceae (5.15%). The largest number of plants was used for the treatment of cuts (40.20%), skin inflammation (37.11%) and rash (37.11%). The aerial parts were the most commonly used (34.75%). The medicinal plant species with larger use values were Heterotheca inuloides (0.53), Aloe vera (0.37) and Oenothera rosea (0.21). The comparison of results with ethnomedicinal literature worldwide revealed that 8.25% of plants used on the Purépecha Plateau were recorded for the first time for the treatment of dermatological affections.Conclusions: This study provides new information on medicinal plants used on the Purépecha Plateau to treat cutaneous diseases. Future pharmacological and toxicological investigations are required to demonstrate the efficacy and safety of these species for treating dermatological affections.